Efficient Discovery Protocol for Ubiquitous Communication in Wireless Environment - Zarrin, Javad (2009)
Nowadays, according to the advances of the wireless network technologies and also mobile computing devices the concept of ubiquitous computing environments has become a considerable research area. Ubiquitous computing environment means an environment which is saturated by elements or devices with capacities of computing and communication. So, there are a lot of ways to develop and employ applications in such environment as infrastructure, but the most effective and general one is using service advertisements, service discovery and service remote invocation. In an Ad-hoc network which its devices make an ubiquitous computing environment, every device as a server node can announce various applications as services in the environment and at the same time every device is able to listen to the network interface and be aware of surrounding services and invoke the remote services.A mechanism which is needed to recognize surrounding services is called service discovery, this mechanism also clears how to advertise services, and invoke them. Type and method of discovery procedures play the critical role in quality and efficiency of services in ubiquitous environments. Because of these properties (small and mobile) there is a serious limitation for the resources of devices specially power resource. The problem is that the most of service discovery protocols are not effective for wireless Ad- Hoc networks and ubiquities environments, efficiency in case of service quality and power consumption. In this research a new mechanism and algorithm is designed to improve current wireless service discovery protocols. Analysis of the results has shown that the designed mechanism in most of the comparative parameters such as speed of service delivery, power consumption, and coverage of the services will act much better than the current discovery protocols. The proposed solution is compared with (directory based and directory-less based) of discovery protocols in ubiquitous environment in three states: mobile nodes, mobile and static nodes, and static nodes. It can be derived that the proposed model obtains fewer messages around 52% while maintain the same rate of service discovery and false rate of service discovery. The reduction of the number of posts per request coupled with the fact that devices with greater time availability transmit more responses in the proposed model, it can be concluded that energy consumption in devices with more restrictions will be decreased.